Phase, microstructure, and wear behavior of Al2O3-reinforced Fe–Si alloy-based metal matrix nanocomposites. (March 2020) - Saxena, Akash; Singh, Neera; Singh, Bhupendra; Kumar, Devendra; Sadasivuni, Kishor Kumar; Gupta, Pallav
In the present work, phase, microstructure, and wear properties of Al2 O3 -reinforced Fe–Si alloy-based metal matrix nanocomposites have been studied. Composites using 2 wt.% and 5 wt.% of Si and rest Fe powder mix were synthesized via powder metallurgy and sintered at different temperature schedules. Iron–silicon alloy specimens were found to have high hardness and high wear resistance in comparison to pure iron specimens. Addition of 5 wt.% and 10 wt.% alumina reinforcement in Fe–Si alloy composition helped in developing iron aluminate (FeAl2 O4 ) phase in composites which further improved the mechanical properties i.e. high hardness and wear resistance. Formation of iron aluminate phase occurs due to reactive sintering between Fe and Al2 O3 particles. It is expected that the improved behavior of prepared nanocomposites as compared to conventional metals will be helpful in finding their use for wide industrial applications.